Examining the Academic Motivation and Academic Procrastination Levels of University Students in the Distance Education Process - Şeker, Ramazan; Köse, Bereket (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2025)
The purpose of this study is to examine the levels of academic motivation and academic procrastination of university students receiving distance education. The universe of the study consists of students studying at Hatay Mustafa Kemal University in the 2024-2025 academic year. The sample group consists of 241 female and 274 male (n=515) students studying at Hatay Mustafa Kemal University (Sports Sciences, Faculty of Education, Faculty of Economics and Administrative Sciences and Fine Arts) within this universe. As data collection tools, personal information was used in the first part, the academic motivation scale developed by Bozanoğlu (2004) was used in the second part, and the Academic Procrastination Scale developed by Çakıcı (2003) was used in the third part. SPSS 22 program was used in the analysis of the research data. For the analysis of the data, t test was used for binary variables, ANOVA test was used to look at the difference between multiple variables and Pearson Product Moment Correlation Analysis was used to determine the relationship between academic motivation and academic procrastination. According to the results of the research, it was concluded that there was a statistically significant difference in the levels of academic motivation and academic procrastination of the students in terms of gender and department variables. When the results of the Pearson product moment correlation analysis were examined to determine the relationship between Academic Motivation and Academic Procrastination, it was seen that there was a positive and significant medium level difference.